If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying w * w + 9 = 6w Multiply w * w w2 + 9 = 6w Reorder the terms: 9 + w2 = 6w Solving 9 + w2 = 6w Solving for variable 'w'. Reorder the terms: 9 + -6w + w2 = 6w + -6w Combine like terms: 6w + -6w = 0 9 + -6w + w2 = 0 Factor a trinomial. (3 + -1w)(3 + -1w) = 0Subproblem 1
Set the factor '(3 + -1w)' equal to zero and attempt to solve: Simplifying 3 + -1w = 0 Solving 3 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1w = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1w = 0 + -3 -1w = 0 + -3 Combine like terms: 0 + -3 = -3 -1w = -3 Divide each side by '-1'. w = 3 Simplifying w = 3Subproblem 2
Set the factor '(3 + -1w)' equal to zero and attempt to solve: Simplifying 3 + -1w = 0 Solving 3 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1w = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1w = 0 + -3 -1w = 0 + -3 Combine like terms: 0 + -3 = -3 -1w = -3 Divide each side by '-1'. w = 3 Simplifying w = 3Solution
w = {3, 3}
| 4x+172=180 | | .3T-2.1C-2.3=7.6 | | 5r+4=9(r-3) | | (m/2)-(1/m)=(6m+5/12) | | X^2+6X=34 | | 15x-75=90 | | Y=(15x+10)(15x-2) | | 3(2a-b)-5a= | | 7v+2=0 | | 2x-4x+4=x-3+7 | | 7=3(t-5)-t | | 3x^2-2x-8=448 | | Y=225x^2+120x+20 | | 1.3x+1.6y=.6 | | 15x-150=90 | | -8-2(8n-8)=-6n+8 | | 5x-2x-3=27 | | -76+n=-115 | | 6tx=4+2 | | 5x-6+6/5=14+6/5 | | 3a+8+a-9-2= | | 15=9w | | 10x+34=114 | | (x+2)2=13 | | -13+3x=-52+24 | | 4cos^2(x)+1=3 | | 5x+6+6/5=16+6/5 | | 8p+2=4-10 | | 5x+59=99 | | 3+2*(-x+4)= | | 6x=-4x^2 | | 16x+68=180 |